Types and Causes of Injuries of Carers of Adults With Intellectual Disabilities: Observational Study. Issue 3 (21st April 2015) - Finlayson, Janet; Jackson, Alison; Mantry, Dipali; Morrison, Jillian; Cooper, Sally‐Ann
Abstract The aim of this research was to investigate the incidence, types, and causes of injury experienced by a community‐based cohort of family and paid carers of adults with ID (n = 446) in Scotland over a 12‐month period, compared with the age and sex‐matched general population in the same geographical area (n = 1, 225). We hypothesized that they would be at an increased risk of injury due to their caring/support role, and particularly as a consequence of caring for adults with ID who present physical aggression. Young and middle‐aged female and older‐aged male carers experienced more injuries in the previous 12 months than did the matched general population, but not significantly so. Contrary to our hypothesis, young and middle‐aged male and older female carers experienced fewer injuries, but this was also not significant. Carers were significantly less likely to experience injury from the use of a tool, implement or equipment (p = .045), and, contrary to our expectations, the carers were not more likely to experience injury from another person's physical aggression (p = .065). Types and causes differed between the carers and the general population. Injuries occur commonly among carers of adults with ID. While carers were not more likely to experience harmful injury from another person's physical aggression, we speculate that the underlying causes of injury are likely to differ between carers and the general population, with the carers being injured due to their carer role. This requires further in‐depth study.